Eksplorasi Artefak Zaman Megalitikum Berdasarkan Citra Bawah Permukaan Menggunakan Metode Geolistrik Resistivitas di Dusun Kendal Desa Kamal Kec.Arjasa Kab. Jember - Arik Irawati; Supriyadi Supriyadi; Nurul Priyantari (Jurnal Fisika FLUX, 2020)
Megalithic age artifacts are spreaded in the Jember region, one of them in the Kendal hamlet adjacent to the Duplang site. There are still many artifacts buried in this location that need to be explored using the geoelectric resistivity method of the Wenner configuration. Data acquisition was carried out on 3 lines with length of 40 m. Base on 2D resistivity distribution image for all three lines, it was known that the subsurface structures were dominated by clay with resistivity value of (1.54 – 89.4) Ωm. Resistivity anomaly with value (197-581) Ωm, which are suspected of being andesite stones forming the artifacts are at a depth (0.25 -3.19) m on the three lines. The presumption existence of the artifacts is reinforced by the presence of kenong rock and menhirs outcrops on line 2.